46 Sulfonation-Based Decontamination Alters Biotransformation and Excretion of Deoxynivalenol in Nursery Pigs. (21st September 2022) - Chen, Chi; Yao, Dan; McGhee, Molly L; Faris, Richard; Giesting, Don W
Abstract: Deoxynivalenol (DON) is a primary mycotoxin in cereal feed ingredients that negatively affects feed intake and immune function of pigs. Formation of DON sulfonate (DONS) with sulfites in feed has become an effective approach to mitigate the DON toxicities in practice, but the metabolic fate of DON under sulfonation-based decontamination was not well defined. In this study, 48 nursery pigs (35 d of age, 10.8 ± 1.3 kg) were stratified by weight and sex and grouped following a 2 x2 factorial design on the DON content in corn-soybean meal diets (1.2 vs. 4.1 ppm) and the inclusion of NoTox Ultimate D, a sulfite-based mitigant (0 vs. 0.25%). Four experimental diets, including low-DON feed with no mitigant treatment (LD-NT); low-DON feed with sulfonation treatment (LD-ST): high-DON feed with no mitigant treatment (HD-NT); high-DON feed with sulfonation treatment (HD-ST), were fed for 21 d for urine collection on day 0, 10, and 21 and fecal collection on day 21. Urine and fecal samples were analyzed by both targeted metabolite analysis and untargeted metabolomic modeling. DON itself was absent in all fecal and urine samples, indicating a complete biotransformation. As expected, sulfonation led to the formation of DONS in feces in correlation with the DON content in feed and the decrease of two DON glucuronides in urine (HD-ST < HD-NT). Interestingly, sulfonation did not decrease the concentrations of two deepoxy-deoxynivalenol (DOM) glucuronides in urine. Instead, it significantly increased DOM in feces (HD-ST > HD-NT). The results indicate that the formation of DONS by sulfite treatment alters the biotransformation and excretion of DON by decreasing the availability of free DON for absorption and simultaneously increasing its availability for microbial metabolism to form DOM, an inactivated metabolite, for fecal and urine excretion.